Impact of Different Carbon Sources on Volatile Organic Compounds (VOCs) Produced during Fermentation by Levilactobacillus brevis WLP672 Measured Using Proton Transfer Reaction Time-of-Flight Mass Spectrometry (PTR-ToF-MS) - Rajendran, S.; Khomenko, L.; Silcock, P.; Betta, E.; Biasioli, F.; Bremer, P. (MDPI, 2024)
Bacterial fermentation is considered to be a cost-effective means of generating desired flavour compounds from plant-based substrates. However, the wide range of substrates present in plants makes it challenging to understand how individual components impact on flavour volatile organic compound (VOC) production. To simplify this, a defined medium can be used to better understand VOCs production with regard to individual compounds. In the current study, the VOCs produced by the lactic acid bacterium, Levilactobacillus brevis WLP672, growing in a defined medium containing different carbon sources (either glucose (DM), fructose (DMFr) or citrate (DMCi)) under a range of fermentation conditions (time: 0, 7, and 14 days; and temperature: 25 and 35 °C) were assessed using proton transfer reaction time-of-flight mass spectrometry (PTR-ToF-MS). Among the detected mass peaks (m/z), after 7 days of fermentation, the concentrations of m/z 45.033 (t.i. acetaldehyde), m/z 49.011 (t.i. methanethiol), and m/z 89.060 (t.i. ethyl acetate) were significantly (p < 0.05) higher in DM at 35 °C than all other treatments at either temperature. The knowledge obtained will help to produce desirable LAB fermentation flavour VOCs or VOC mixtures that could be used in developing plant-based analogues with acceptable sensory properties.T8 (100% IF + VW). T1 and T2 also showed comparable net benefits to T8 and T9. Therefore, this concluded that the combined application of vermicompost, inorganic fertilizers, and vermiwash significantly enhances Amaranthus growth and yield, compared to control and chemical fertilizers alone highlighting the potential of integrated nutrient management for sustainable agriculture.
Keywords: Carbon sources; Defined medium; Lactic acid bacteria (LAB); Volatile organic compounds